Cardiac β‐adrenergic receptor activation mediates distinct and cell type‐dependent changes in the expression and distribution of connexin 43. Issue 15 (24th June 2020) - Zhang, Yi; Hou, Meng‐Chen; Li, Jing‐Jing; Qi, Ying; Zhang, Yu; She, Gang; Ren, Yu‐Jie; Wu, Wei; Pang, Zheng‐Da; Xie, Wenjun; Deng, Xiu‐Ling; Du, Xiao‐Jun
Abstract: Activation of the sympatho‐β‐adrenergic receptors (β‐ARs) system is a hallmark of heart failure, leading to fibrosis and arrhythmias. Connexin 43 (Cx43) is the most abundant gap junctional protein in the myocardium. Current knowledge is limited regarding Cx43 remodelling in diverse cell types in the diseased myocardium and the underlying mechanism. We studied cell type‐dependent changes in Cx43 remodelling due to β‐AR overactivation and molecular mechanisms involved. Mouse models of isoproterenol stimulation or transgenic cardiomyocyte overexpression of β2 ‐AR were used, which exhibited cardiac fibrosis and up‐regulated total Cx43 abundance. In both models, whereas Cx43 expression in cardiomyocytes was reduced and more laterally distributed, fibroblasts exhibited elevated Cx43 expression and enhanced gap junction communication. Mechanistically, activation of β2 ‐AR in fibroblasts in vitro elevated Cx43 expression, which was abolished by the β2 ‐antagonist ICI‐118551 or protein kinase A inhibitor H‐89, but simulated by the adenylyl cyclase activator forskolin. Our in vitro and in vivo data showed that β‐AR activation‐induced production of IL‐18 sequentially stimulated Cx43 expression in fibroblasts in a paracrine fashion. In summary, our findings demonstrate a pivotal role of β‐AR in mediating distinct and cell type‐dependent changes in the expression and distribution of Cx43, leading to pathological gap junction remodelling in the myocardium.